2023
DOI: 10.1002/hed.27370
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical classification of pharyngeal and laryngeal endoscopic images using artificial intelligence

Abstract: Background The entire pharynx should be observed endoscopically to avoid missing pharyngeal lesions. An artificial intelligence (AI) model recognizing anatomical locations can help identify blind spots. We developed and evaluated an AI model classifying pharyngeal and laryngeal endoscopic locations. Methods The AI model was trained using 5382 endoscopic images, categorized into 15 anatomical locations, and evaluated using an independent dataset of 1110 images. The main outcomes were model accuracy, precision, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Researchers have observed that such patients are more prone to PCF. Endoscopic observation can detect potential PCF early and prevent PCF 31 . There are various methods for prevention and treatment of pharyngeal cutaneous fistula, so it is very important to find out the risk factors and healing factors for the occurrence and development of laryngeal cutaneous fistula after total laryngectomy for laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have observed that such patients are more prone to PCF. Endoscopic observation can detect potential PCF early and prevent PCF 31 . There are various methods for prevention and treatment of pharyngeal cutaneous fistula, so it is very important to find out the risk factors and healing factors for the occurrence and development of laryngeal cutaneous fistula after total laryngectomy for laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) assisted computer vision during flexible laryngoscopy provides valuable insights and facilitates diagnosis. [7][8][9][10] Investigators have used deep learning models to classify vocal fold pathology, 11,12 localize lesions in the endoscopic field, 13,14 and evaluate images for diagnostic quality. [15][16][17] Most of these applications focus on static endoscopic images; there are few reports of video annotation models.…”
Section: Introductionmentioning
confidence: 99%